The role of convective heat transfer coefficient in CuO nanoparticles-PCM cooling ability in heat sinks with insulated side walls: comparison with the air cooled one - Abu-Hamdeh, Nidal H.; Melaibari, Ammar A.; Alquthami, Thamer S.; Khoshaim, Ahmed; Öztop, Hakan Fehmi; Golmohammadzadeh, Ali (Springer, 2021)
In this study, the effectiveness of the heat sink with an insulated wall equipped with nano-PCM and air-cooled one was compared. Heat sink effectiveness was defined as the ability of the heat sink to keep lower the base temperature. It was found that for each heat sink, a critical heat transfer coefficient can be supposed. If the convective heat transfer coefficient is less than the critical value, the effectiveness of the nano-PCM filled heat sink is superior to that of the air-cooled one up to the end of the melting time. Otherwise, it is recommended to use the air-cooled heat sink. A novel correlation was proposed to estimate the critical value, and it was shown that the closer the melting temperature to the ambient, the higher the critical value which means the greater the ability of the PCM-HS to compete with air-cooled one.
Keywords: PCM filled heat sink; Air-cooled heat sink; Convective coefficient